2018-2020-2021 Panel data CSA Monitoring Guatemala and Honduras- demographic, climate, empowerment and social capital modules - Paez Valencia, Ana Maria; Howland, Fanny C.; Moreno Bustamante, Manuel Francisco; Bonilla Findji, Osana Carmela Pilar; Martínez Barón, Deissy; Martínez Salgado, Jesús David; López, Claudia; Guevara, Melvin; Álvarez Espinosa, Osman; Eitzinger, Anton (2023)
This data set contains responses to surveys conducted with participants of Climate Smart Villages in Honduras and Guatemala for the years 2018-2020-2021. The data includes information at the individual level from surveys conducted with a total of 1,511 individuals throughout the three periods. The data presented has sociodemographic information, gender, social capital and climate services.